How Product and Manufacturing Design Enable Sustainable Companies and Societies 2022
DOI: 10.35199/norddesign2022.38
|View full text |Cite
|
Sign up to set email alerts
|

Morpheus: The Development and Evaluation of a Software Tool for Morphological Matrices

Abstract: The Morphological Matrix is a well-known and established method for synthesising concepts in engineering design. With the aim to improve its applicability, the method has been implemented into a software tool, which then has been introduced in engineering courses at Chalmers University of Technology. In this paper, the tool and its most important functions are presented and discussed, along with experiences from its use in design projects. It was demonstrated that the tool can ease the process of creating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The industrialisation of engineering methods has long been an observed issue and it is important that the user understands how to use the method and its purpose (Eder 1998;Araujo et al, 2007). One computerized Morphological Matrix tool called Morpheus (Martinsson et al (2022) is provided by the DSIP, and it has previously demonstrated cases where the tool is misunderstood and misused in university courses. There is thus a need to validate that the current method-and tool-specific information provided by DSIP is sufficient to ensure intended use.…”
Section: Concluding Discussion and Future Workmentioning
confidence: 99%
“…The industrialisation of engineering methods has long been an observed issue and it is important that the user understands how to use the method and its purpose (Eder 1998;Araujo et al, 2007). One computerized Morphological Matrix tool called Morpheus (Martinsson et al (2022) is provided by the DSIP, and it has previously demonstrated cases where the tool is misunderstood and misused in university courses. There is thus a need to validate that the current method-and tool-specific information provided by DSIP is sufficient to ensure intended use.…”
Section: Concluding Discussion and Future Workmentioning
confidence: 99%
“…While converting already established design approaches into software can give rise to opportunities of enriching the pre-existing approaches, it first needs to be validated that this step into the digital realm has merit (Isaksson et al, 2020). Digitalizing and automating methods that have traditionally been conducted manually can have unintended side-effects (Martinsson Bonde et al, 2022). It is therefore necessary to conduct thorough evaluations of such digital tools to better understand the implications and address any negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…This tool was initially introduced to first year mechanical engineering students. However, the quality of the output from Morpheus generated by the students was found to be quite low, in that the generated solutions were rarely developed beyond the mere combination of SSs identified using the MM (Martinsson Bonde et al, 2022). In the 2022 study, the students would often use Morpheus to generate an unmanageable quantity of SS combinations, and refrain from describing them any further.…”
Section: Introductionmentioning
confidence: 99%